Organizacje ekologiczne w postępowaniu administracyjnym w sprawie wydania pozwolenia wodnoprawnego - Kański, Dawid (Studia Prawa Publicznego, 2025)
The article addresses the issue of environmental organizations in administrative proceedings concerning the granting of water law permits. The starting point is a discussion of the concept of an environmental organisation, the definition of which has been shaped by case law and environmental law doctrine. Discussing the issue also requires an analysis of the evolution of the provisions of the Water Law, which initially completely excluded environmental organisations from proceedings concerning the granting of water permits; only as a result of an amendment was their participation allowed, although it should be noted that this was to a limited extent. However, despite the amendment, the scope of participation of environmental organisations remains narrow and covers only proceedings for the issuance of a water permit, preceded by a decision on environmental conditions. However, this type of regulation still limits the possibility of social control over the ecological condition of waters. In this context, a significant problem is the controversy surrounding the abuse of the law by environmental organisations, which is sometimes used to prolong administrative procedures or achieve extra-legal goals, thus, goals that are not in the public interest. While the above circumstances may justify limiting the procedural rights of environmental organisations, it should be noted that there are instruments in the Polish public law system to counteract such practices. This, in turn, may provide grounds for granting environmental organisations broader powers than before. In light of the above, it seems reasonable to propose expanding the participation of environmental organisations in proceedings concerning water law permits, while introducing mechanisms to prevent abuse.